Barriers to the vaccination of children and adolescents and possible solutions. (24th January 2014) - Esposito, S.; Principi, N.; Cornaglia, G.; ,
Abstract: The benefits of vaccination are clearly demonstrated by the eradication or enormous decline in the incidence of many vaccine‐preventable diseases, but the coverage of many highly recommended vaccines is still frequently inadequate and children continue to suffer from diseases that could have been prevented. The main aim of this paper is to discuss the recognized barriers to the vaccination of children and adolescents confronting national health systems, providers and parents, and the ways in which they can be overcome. Most of the problems underlying limited vaccination coverage among children are due to a lack of understanding on the part of healthcare providers and parents, which underlines the need for educational programmes specifically addressed to each of these groups. It is also essential that all of the physicians providing immunization develop approaches that acknowledge parents' concerns and respectfully try to correct any misinformation. Other means of extending vaccine coverage include the implementation of adequate systems for recording vaccine administration and the activation of effective reminder/recall systems, the provision of immunization services in some medical care specialties or by integrating healthcare sites, and the elimination or reduction of all the problems that currently limit access to vaccination services. However, it will take the combined efforts of healthcare systems and providers to pull down all of the barriers.